Budaya Organisasi terhadap Kepuasan Kerja Karyawan - Ananda Adjang Ardam; Sutarto Wijono (Kuras Institute, 2022)
This study aims to determine the effect of organizational culture on job satisfaction of employees of company which is engaged in retail. Participants in this study were employees who worked at company with a total population of 32 participants. The research method used in this study is a quantitative approach, with a non-probabilty sampling technique, namely saturated sampling by taking the entire population of 32 participants. Measurement of organizational culture uses a scale from Hartanto (2016) which develops a scale from Robbins (2011) to measure organizational culture with a cronbach alpha of 0.856. Meanwhile, to measure job satisfaction using a job satisfaction scale according to Spector (1997) with a cronbach alpha of 0.791. The scale is distributed in the form of a questionnaire, with data analysis using IBM SPSS Statistics version 26 and simple linear regression analysis with the equation Y= a + bX. The results of data analysis obtained the equation Y = 30,754 + 0.110 X. This means that the results of the study found that organizational culture had a significant effect on employee job satisfaction at company. Thus the research hypothesis which reads that there is a significant influence of organizational culture on employee job satisfaction at company accepted.